Contribuições da diversidade geracional para a aprendizagem organizacional - Colet, Daniela Siqueira (2016)
The generational diversity that forms the workforce on organizations, characterized by its relational exchanges and interactions, has the potentiality of constituting knowledge-rich organizational environments that are capable of contributing to the organizational learning (OL). Most of the scientific studies about OL in Brazil are based on psychological perspective (predominantly cognitivist and experiential) and on Administration perspective, having also a strong influence of the economic bias. With the purpose of transposing the pragmatic lines of thought, it was worked in this dissertation a sociologic perspective, in which the analysis of the organizational practices undertakes relevance and leads to the progress of the OL studies, as a central explanatory point of this phenomenon. When considering that the processes of learning are not only cognitive, but also physical and multi-sensorial, the use of an aesthetic approach was adopted. The question that guided this study was: under the sociological perspective, how does the generational diversity contributes to the OL? Considering this problematic, the main objective of this dissertation was to propose an analytical schematic concept that would facilitate the comprehension of the generational diversity contributions to the OL, under the sociological perspective. Aiming to achieve the outlined objective, a qualitative research was held, with an exploratory and descriptive nature, through which was performed a multiple case study in two large companies in the city of Marau – RS. The data were collected through differentiated techniques, covering twenty five participants: semistructured interviews, life stories, focus group and non-participant observation. These data were analyzed by means of content analysis, and all the process was supported by the qualitative data analysis computer software NVivo®10. With the application of an analytical schematic concept, the achieved results revealed that the learning occurs on daily work practices, through social relations and interactions. On a procedural relation will happen the exchange of knowledge, experiences, ideas and suggestions, which will further new practices, new working methods, and new knowledge, resulting on a new intergenerational learning that contributes to OL. The research showed that there are other elements involved in the behaviors and not only generational difference, evidencing the importance of considering the profile of the workers, the social class and the histories of each one. The findings refer to the importance of not having as a focus the antagonism of the generational diversity, which some current publications still suggest, but adopting a relational analysis focusing the coconstruction and the complementarity of the multi-generational conviviality in organizations, such as useful relations which generate intergenerational learning and OL.